Evaluation of Staphylococcus aureus Subtyping Module for Methicillin-Resistant Staphylococcus aureus Detection Based on Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry - Hu, Yanyan; Huang, Yonglu; Lizou, Yangzi; Li, Jiaping; Zhang, Rong (Frontiers in Microbiology, 2019)
A recent developed S. aureus subtyping module for rapidly differentiate methicillin-resistant Staphylococcus aureus (MRSA) from methicillin-susceptible S. aureus (MSSA) had been introduced into China. The principle of this method was to identify the methicillin resistance through detection of a specific phenol soluble modulin-mec peak (PSM-mec) by matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS). A total of 347 non-duplicated S. aureus strains were collected from the Second Affiliated Hospital of Zhejiang University School of Medicine during January 2014 to February 2019. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the automated subtyping module in identifying MRSA were evaluated. The specificity and PPV of this method were both 100% and the sensitivity was 60.2%. PSM-bearing MRSA were reported with different prevalence from different parts of world, our sample collection has the highest percentage so far. The repeatability showed that 1.7% (6/347) and 18.4% (64/347) were reported differently in the intra- and inter- batch analysis, respectively, which demonstrated that the threshold of this method could be further optimized to increase the sensitivity of MRSA detection. Overall, Bruker™ MALDI Biotyper can detect S. aureus isolates with a quite high specificity and expedite the identification of MRSA isolates without using extra reagent, labor or time. The reduced turnaround time of MRSA identification is essential for appropriate therapeutic management and timely intervention for infection control.